Comparing some blood parameters of ski racers and long-distance athletes - Banu Can; Metin Bayram; Gökhan Bayraktar; Harun Akyol (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to make a comparison of some blood parameters of the elite level strength athletes in two different branches. Sixty male and female sedentary and national elite level athletes in the range of 18-22 years voluntarily participated in this research. 60 volunteers were divided into 3 groups as the control group (10 males, 10 females), the experimental group 1 (10 males, 10 female athletes) and the experimental group 2 (10 males, 10 female ski runners). Blood samples were taken at the resting state after briefing the test subjects during the period of competition. The subjects were warned a day before measurements not to take any food and drink from the evening at 22:00. 5 ml blood samples taken from the forearm were collected in EDTA tubes at 10.00-11.00am and biochemical analyzes were performed at the Central Laboratory of Biochemistry in Agri State Hospital. Obtained data were analyzed and evaluated in SPSS 19.0. In the analysis, Shapiro Wilk, Mann-Whitney and Kruskal-Wallis tests were used. According to the biochemical results of male athletes, while there is no significant correlation between the values of Glucose, ALT, Triglycerides, Cholesterol, HDL, LDL, FE Binding Capacity, Creatinine Kinase and MG, a significant correlation were found in the BUN value between skiers with athlete and control groups, in the Albumin value between athlete and control groups, in the NA value between athlete and control groups, in the AST value between athlete and skiers groups, in uric acid value among all groups, in CA value among all groups, in creatinine value among all groups. According to the biochemistry results of female athletes located in skiers, athlete and control groups, a statistically significant difference was observed between control and skier groups in terms of CA value (p=0.04). There are meaningful differences between the control and athlete groups and between control and skier groups in terms of Creatinine Kinase value (p=0.00). There was not any significant correlation between the groups compared to the other parameters. When athletes in the control and experimental groups were compared among themselves, significant differences have been found in some blood parameters but it has not been observed any differences in some other parameters.